Optimizing germination conditions to enhance the accumulation of bioactive compounds and the antioxidant activity of kiwicha (Amaranthus caudatus) using response surface methodology - Paucar-Menacho, Luz María (2017)
Controlled grain germination is a method of emerging interest to naturally improve nutritional and nutraceutical profile of grains. The aim of this study was to optimize germination temperature and time using response surface methodology to maximize the concentration of ɣ-amminobutyric acid (GABA), phenolic compounds (PC) and the antioxidant activity of kiwicha (Amaranthus caudatus) grains. The optimal germination temperature and time were 26 °C and 63 h, respectively, in which GABA, PC and antioxidant activity increased 29.1, 4.0 and 6.4-fold, respectively. Individual phenolic composition of kiwicha sprouts obtained in the optimal conditions was analyzed by HPLC-DAD-ESI/MS. Sprouting in the optimal germination conditions enhances mainly the concentrations of 4-O-caffeoylquinic, 4-O-feruloylquinic acids and quercetin-3-O-rutinoside. Predicted models were significant (P < 0.05) for all the parameters studied with high regression coefficients ranging from 0.965 to 0.989. The predicted values from the developed quadratic polynomial equation were in close agreement with the experimental values. In conclusion, germination at 26 °C for 63 h offers a practical opportunity for enhancing the nutraceutical quality of kiwicha grains supporting their preferential use over non-germinated grains for improving health outcomes associated to lifestyle-associated diseases. © 2016 Elsevier Ltd